Design of Microstrip Inter-Digital Capacitor Using Particle Swarm Optimization - Noora Mohammad Sadiq; Sadiq K. Ahmed (Journal of Engineering and Sustainable Development, 2025)
In this work, an inter-change capacitor design is developed using the particle swarm optimization technique. The PSO improves the inter-digital capacitor filter characteristics by varying capacitance geometry parameters. The capacitance value will vary greatly depending on the intended scale (in mm) for physical characteristics such as the number of fingers, finger width, and finger length. After executing the PSO algorithm for a predetermined number of iterations, the maximum capacitance value closest to the intended value is obtained. The optimization process was implemented in MATLAB and validated via full-wave simulations in HFSS at 1 GHz. The PSO algorithm achieved convergence within 50 iterations and produced capacitance values ranging from 0.48 pF to 0.92 pF, closely matching the desired targets with an average error of less than 2%. Results demonstrated that increasing the number and length of the fingers while reducing the gap between them significantly improved capacitance density. Compared with traditional trial-and-error and ANN-based approaches, the proposed PSO method reduced the design time by approximately 40% while maintaining high computational efficiency. The developed algorithm offers a simple mathematical formulation, fast convergence, and practical accuracy, making it a reliable optimization tool for high-frequency and RF/microwave circuit applications.